Akuntabilitas Pemimpin Pendidikan Berbasis Agama, Filsafat, Psikologi Dan Sosiologi - Achmad Saefulrijal; Faiz Fatkhullah; Indri Lastriyani; Ida Farida Fitriyani (Smart Education, 2023)
Abstract: This study aims to describe and analyze the accountability of educational leaders based on religion, philosophy, psychology and sociology. 1). Based on the religion of Allah SWT as a result of an education that is fair, kind, satisfying, not deceptive, not against rules and not self-contradictory. 2). What is philosophically grounded is a moral responsibility to the rules of logical reasoning that arise from educational acts that must be carried out with substantive, sustained, practical, progressive and reconstructive diligence. . 3). Psychology is based on the emotional responsibility of feeling human about something, the correct character, behavior, and educational actions that should be taken in situations. Four). Sociology is grounded in social responsibility to social status through education and must be practiced in ways that meet the functional needs of society and the stratification of political, economic and social status.Keywords: educational accountability, religion-based accountability, philosophy-based accountability, psychology-based accountability, sociology-based accountability, leaders.Abstrak: Penelitian ini bertujuan untuk medeskripsikan dan menganalisis akuntabilitas pemimpin pendidikan berbasis agama, filsafat, psikologi dan sosiologi. 1). berbasis berdasarkan agama kepada Allah SWT sebagai akibat dari suatu tindakan pendidikan yang harus adil, baik hati, memuaskan, tidak menipu, tidak melanggar aturan dan tidak bertentangan dengan dirinya sendiri. 2). berbasis filsafat adalah tanggung jawab mental untuk aturan berpikir logis akibat dari suatu tindakan pendidikan yang harus dilakukan dengan hati-hati substansial, abadi, pragmatis dan progresif dan rekonstruktif. 3). berbasis psikologi adalah tanggung jawab emosional untuk merasakan manusia tentang sesuatu tindakan pendidikan yang harus dilakukan dengan hati-hati karakter, perilaku, dan situasi yang tepat di sekitarnya. 4). berbasis sosiologi adalah tanggung jawab sosial atas kedudukan sosial melalui pendidikan, harus dilakukan dengan cara yang memenuhi kebutuhan fungsional masyarakat, stratifikasi status politik, ekonomi dan sosial.Kata kunci: akuntabiltas pendidikan, akuntanbilitas berbasis agama, akuntabilitas berbasis filsafat, akuntabilitas berbasis psikologi, akuntabilitas berbasis sosiologi, pemimpin.